A Comparative Efficacy and Adverse Clinical Events of Methotrexate versus Azathioprine with Steroid Mini Pulse Therapy in the Management of Moderate to Severe Alopecia Areata: A Tertiary Centre Based Interventional Study - Aditi Mishra; Shekhar KC; Elisha Shrestha; Chandranshu Pandey; Dharmendra Karn (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Alopecia areata is a T cell-mediated autoimmune disorder of hair follicles resulting in partial or total hair loss. Treatment of alopecia areata is difficult, and it has variable severity.